Optimizing Democracy: The Political Law of Digitization Policy for the Prevention of Election Disputes in Indonesia - Khoirunnisa; Jubaidi, Didi (Ilomata International Journal of Social Science, 2024)
General elections in Indonesia have undergone a significant transformation through the adoption of information technology and digitalization. This transformation not only accelerates the voting process, but also has a major impact on the legal regulations governing elections. In this context, the Political Law of Digitalization Policy plays an important role in shaping an effective regulatory framework, especially in dispute prevention. The application of technology in elections should not leave behind some people who are not familiar with digital devices. Therefore, regulations should detail measures to ensure that every citizen has a fair and equal opportunity to participate in the electoral process. Regulations should provide a clear framework for handling complaints, checking discrepancies, and ensuring that election results are acceptable to all parties. Through the adoption of information technology and digitization, it reinforces the political urgency of the policy law. This study aims to determine the contribution of the Election Digitalization Policy in reducing risks and handling potential disputes in general elections. The method used in this research is normative juridical. The results show that the Political Law of Digitalization Policy has a central role in shaping regulations that support modern, inclusive, and dispute-free elections in the digital era. Through this approach, it is expected that Indonesia can move towards more efficient and trustworthy elections. The implementation of election digitization has an impact on increasing transparency and public trust, efficiency and accuracy, accurate data recording, simplifying the electoral process, preventing fraud, and reducing the burden on the Constitutional Court.